The Influence of Parenting Styles (Authoritarian, Democratic, and Permissive) on the Independence of Group B Children at KB Al Fatih Banyuasin III - Melinda, Herzamia Tria; Rukiyah, Rukiyah (Journal of English Language and Education, 2025)
Early age is an important phase for developing independence in children, where they learn to manage daily activities without the help of others, such as eating and dressing. This independence includes physical, emotional, and social aspects, which are greatly influenced by parental parenting patterns. This study aims to determine the effect of parental parenting patterns on the independence of group B children at KB Al Fatih Banyuasin III. The independent variable is parental parenting patterns while the dependent variable is child independence. The type of research uses quantitative with the Ex Post Facto method. The sample consisted of 53 parents of children who attended KB Al Fatih Banyuasin III, with data collection techniques using questionnaires. Data analysis used in the hypothesis test is simple linear regression analysis. The test results show that parental parenting patterns on the independence of Group B children at KB Al Fatih Banyuasin III show that parental parenting patterns have a significant effect on child independence. Judging from the results of the t-test, the calculated t value is 8.199 t table 2.008, so H0 is rejected and Ha is accepted and the results of the determination coefficient explain that the magnitude of the influence of the parenting pattern variable on the child's independence variable is 56.9% while 43.1% comes from other influences.